2018
DOI: 10.3233/wor-182810
|View full text |Cite
|
Sign up to set email alerts
|

Returning to work after breast cancer: A systematic review of reviews

Abstract: BACKGROUND: Due to improvements in breast cancer diagnosis and treatment, the healthcare system faces a growing number of cancer survivors. Breast cancer survivors experience many difficulties when returning to work, including discrimination at work and lack of support by employers and colleagues. OBJECTIVE: To point out the knowledge in literature up to date about return to work (RTW) after breast cancer, the factors influencing it and the interventions to facilitate it. METHODS: A literature search was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 32 publications
5
62
2
3
Order By: Relevance
“…Previous studies have suggested that after BC diagnosis, sociodemographic factors (eg, age, country of birth, and educational level) are associated with a higher risk of SA, DP, not returning to work, and unemployment . Surprisingly, after making adjustments, we did not find any significant association between women's sociodemographic characteristics (including age, country of birth, educational level, family situation, living area, and occupational sector) and future high levels of SA/DP days (ie, >90 or >180 days/year).…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Previous studies have suggested that after BC diagnosis, sociodemographic factors (eg, age, country of birth, and educational level) are associated with a higher risk of SA, DP, not returning to work, and unemployment . Surprisingly, after making adjustments, we did not find any significant association between women's sociodemographic characteristics (including age, country of birth, educational level, family situation, living area, and occupational sector) and future high levels of SA/DP days (ie, >90 or >180 days/year).…”
Section: Discussioncontrasting
confidence: 90%
“…Breast cancer (BC) is the most commonly diagnosed cancer in women worldwide, with approximately 2 million new cases in 2018 . Approximately half of women diagnosed with BC are of working age; most of these women survive, and a large number of them return to work after treatment …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, reasons for impaired RTW are manifold, comprising health-related, economic, job-related, socio-demographic and psychological factors, and individual preferences (Cocchiara et al., 2018;Islam et al, 2014;Sun et al, 2017). Some of the factors influencing RTW cannot be modified.…”
Section: )mentioning
confidence: 99%
“…Systematic reviews have shown that RTW of people with current or previous cancers is associated with multiple factors [1,3,[30][31][32]. The following factors have repeatedly been shown to be of significance in the RTW-process of cancer patients: personal factors (e.g., socioeconomic factors), health-related factors (e.g., physical and mental health), illness-and treatment-related factors (e.g., type of cancer, type of treatment), and work-related factors (e.g., work demands, type of work, working environment) [1][2][3]32].…”
Section: Introductionmentioning
confidence: 99%